Розвиток та сучасна ситуація комп'ютерних ігор жанру інтерактивне кіно - Бірюков, А. І. (ХНУРЕ, 2024)
The idea of interactive cinema emerged long before the era of gaming con soles and smartphones. The concept of choice-driven cinema was first show cased at the 1967 World Exposition in Montreal, Canada. The Czechoslovak black comedy "The Man and His House," created using the Kinoautomat technology, was presented in a special hall where armrests were equipped with two buttons - red and green. The technology of that time significantly exceeded its era; only one film was produced using it, and it was screened approximately 10 times over half a century.
Keywords: інтерактивне кіно; комп'ютерна гра